INP VEGETASI DAN KARBON TERSIMPAN PADA HKm BINA WANA KECAMATAN KEBUN TEBU KABUPATEN LAMPUNG BARAT - Anis Ambarwati; Duryat Duryat; Wahyu Hidayat (Lambung Mangkurat University-Indonesia, 2019)
Community forest of Bina Wana is one of the forest areas in West Lampung which is divided into three land covers namely primary forest, agroforestry, and annual crops. The differences amoung the land cover affect the ecological role, therefore it is important to figour out the carbon stock in order to determine the potential of environmental services. The purpose of the study was to find out the important values index and carbon stock in community forest of Bina Wana. Sampling was taken using the cluster sampling method based on differences in land cover classes. Carbon stock was estimeted by using allometric equations and biomass calculation. The result of the research showed that the highest important values index in primary forest for tree phase was Joho (Terminalia bellirica) (53,35%), for pole phase (24,23%), sapling (171,18%) and understorey (67,08%), namely Tenam species (Shorea platiclados). The highest important values index on agroforestry was Cempaka (Michelia champaca) (54,37%) to tree, Pulai (Alstonia scholaris) (120,48%) to pole, Coffee (Coffea canephora) (214,45%) to sapling, and Wedusan (Ageratum conyzoide) (105,68%) to understorey. As with the annual crop land, only rice plants (Oryza sativa) (200%) were found in the understorey phase. The average carbon stock for primary forest were (284,15 tons / ha), agroforestry (74,89 tons / ha) and annual crops (1.42 tons / ha) with total carbon stock of fore whole area was (360,46 tons / ha)